2012
DOI: 10.1097/phm.0b013e318238a390
|View full text |Cite
|
Sign up to set email alerts
|

Tracheostomy Management Skills Competency in Physical Medicine and Rehabilitation Residents

Abstract: This educational unit was developed to instruct physical medicine and rehabilitation residents on tracheostomy management in non-ventilator-dependent patients and to implement an objective assessment format to measure the attainment of these skills. Thirty-one subjects participated in a 2-day didactic and hands-on workshop supervised by an attending physiatrist, certified speech pathologists, and registered nurses. Assessment tools developed for this program address the basic competencies outlined by the Accre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 11 publications
4
19
0
Order By: Relevance
“…Similar results from other studies 15,18,22,23 indicate that health care providers are generally not comfortable caring for patients with a tracheostomy and lack an understanding of critical tracheostomy concepts. Smith-Miller 27 evaluated the comfort level of ICU graduate nurses before and after a tracheostomy educational session and found that baseline knowledge and comfort level were low (5.95 on scale 1-10; where 1 ¼ very comfortable and 10 ¼ very uncomfortable).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similar results from other studies 15,18,22,23 indicate that health care providers are generally not comfortable caring for patients with a tracheostomy and lack an understanding of critical tracheostomy concepts. Smith-Miller 27 evaluated the comfort level of ICU graduate nurses before and after a tracheostomy educational session and found that baseline knowledge and comfort level were low (5.95 on scale 1-10; where 1 ¼ very comfortable and 10 ¼ very uncomfortable).…”
Section: Discussionsupporting
confidence: 80%
“…Current ACGME program requirements for pediatrics do not include routine or emergency tracheostomy management as a competency . Recently, Khademi et al demonstrated that educational and hands‐on skills sessions enhanced knowledge and improved skills in managing tracheostomies among physical medicine and rehabilitation residents. Several studies report that pediatric residents are not proficient in airway management skills .…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis was supported by the significant improvement in comfort and skills test scores. Our participant pre‐test scores were comparable to others demonstrating that health care providers have opportunities to improve their emergency response skills. Participants demonstrated lower scores on the self‐assessment of comfort scores which suggests that HCS are aware of the need for ongoing skill development, and seek to improve their confidence and knowledge.…”
Section: Discussionsupporting
confidence: 72%
“…Our program is the first to describe this short, risk focused, simulation program focusing on tracheostomy, and ventilator care specifically designed for HCS. Others have described the use of didactic and simulation methods to teach primary care physicians, residents, and advanced practice nurses tracheostomy care and management skills, however, none of these have included ventilator management. While tracheostomy skills are important, mastery of tracheostomy management skills alone would not achieve the goal of improved patient safety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation